Field Experiences Provide Value for Library Students, but More Research Is Needed into Their Administration - Medaille, Ann (Evidence Based Library and Information Practice, 2011)
Objective – To evaluate an eight-week practicum requirement for library and information science students. Design – Survey questionnaire. Setting – The University of the Punjab and participating libraries in Pakistan. Subjects – A total of 118 graduates of the library and information science program at the University of the Punjab who had completed an eight-week-long practicum experience in a public, academic, or special library between 2002 and 2006. Methods – Snowball sampling was used to select the subjects. Surveys were delivered and collected through personal visits, email, and postal mail, and the authors asked follow-up questions of some subjects whose surveys were collected in person. The survey contained questions about several topics, such as the type of professional tasks (e.g., acquisition, circulation, reference service, etc.) that students did during the practicum, professional skills developed, practicum length, comfort in sharing problems with supervisors, and the evaluation process. The authors used statistical analysis software (SPSS, version 12) to analyze the survey results. Main Results – The majority of subjects reported that they had received the opportunity to train in several sections and functions of the library, and they felt that the practicum was important in improving their professional skills. Most reported being comfortable sharing problems with their supervisors and were satisfied with the evaluation process. The survey also included open-ended questions about problems and suggestions, but only 28% of the subjects responded with comments. Conclusion – The authors concluded that the library practicum plays an important role in the professional development of future library professionals, and that the length of the practicum should be extended from its current eight-week requirement.